2016
DOI: 10.1111/ane.12652
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis, discerning depression from cognition

Abstract: Cognitive impairment is common in multiple sclerosis (MS), affecting up to 70% of patients. One of the most important possible confounders to cognitive assessment is the occurrence of depression, a common consequence of MS. Cognition and depression have been linked in recent neuropsychiatric research that proposed a number of neurocognitive models of mood disorders. According to these models, primary failure of key brain regions of emotional processing and regulation or abnormal connectivity between them contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
1
9
1
Order By: Relevance
“…In contrast to previous data, 32 the applied battery of tests did not reveal an association between depression and cognition in the current study. This might be due to the mild severity of both or be attributed to a short disease duration with preserved cognition leading to patients with depression still performing well in cognitive screening.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to previous data, 32 the applied battery of tests did not reveal an association between depression and cognition in the current study. This might be due to the mild severity of both or be attributed to a short disease duration with preserved cognition leading to patients with depression still performing well in cognitive screening.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study we observed moderate levels of depression in both groups, but depressive symptomatology, and particularly somatic symptoms, improved only in the ITG group. This finding underlines the link between depression and cognitive performance in MS ( Portaccio, 2016 ). At the behavioral level, depression seems to alter attentional capacity, working memory and executive functions.…”
Section: Discussionsupporting
confidence: 72%
“…At the behavioral level, depression seems to alter attentional capacity, working memory and executive functions. This interaction is not surprising, considering the overlap between emotional regulatory regions and the executive network, and the results of neuroimaging studies in depressed patients with MS reporting an involvement of frontal areas ( Portaccio, 2016 ). However, a dysexecutive syndrome secondary to MS might precipitate depression, by altering emotional processing and favoring use of maladaptive cognitive strategies.…”
Section: Discussionmentioning
confidence: 90%
“…Depression and anxiety appear to worsen memory, processing speed and executive functioning in people with MS. 105 107 , 138 , 139 …”
Section: Introductionmentioning
confidence: 99%